Platelets in invasive aspergillosis: role in pathogenesis and immune defense - N. B. Serebryanaya; P. P. Yakutseni; N. N. Klimko (Журнал инфектологии, 2019)
Invasive aspergillosis (IA) is a serious disease, with mortality rate up to 80%. A. fumigatus is an angiovasive pathogen, fragments of its hyphae can detach and circulate in the bloodstream. Platelets are activated by surface structures, metabolites and soluble fungal complexes, resulting in adhesion to conidia and fungal hyphae. The melanin and hydrophobin contained in the conidia, as well as the galactosaminogalactan contained in the hyphae and the glyphotoxin secreted by the hyphae, suppress phagocytic cells, but activate the platelets. Activated platelets show direct antifungal activity by releasing microbicidal proteins and serotonin. In addition to direct antifungal effect, platelets form an interactive network with cellular components of the immune system and a complement system, increasing the response of neutrophils and monocytes. In the presence of platelets, the efficacy of antimycotics is greatly enhanced. The adverse effects of platelet activation in IA are associated with clinical conditions such as hemoptysis, pulmonary hemorrhage and infarctions of various organs. Another danger associated with IA is the development of thrombocytopenia. Thrombocytopenia is defined as an independent risk factor of mortality in IA in oncohematological patients after allogeneic transplantation of hematopoietic stem cells. Numerous evidences of the important role of platelets in protection from A. fumigatus suggest that the study of the number and functional state of platelets will provide a new data, which will help develop new methods for prediction and treatment of IA.